2004
DOI: 10.1021/jp0476040
|View full text |Cite
|
Sign up to set email alerts
|

A Butane Analogue, 3-Hexyne, Is Eclipsed

Abstract: In ethane the facts of a staggered equilibrium structure and a 2.9 kcal/mol torsional barrier are established. 1 However, the origin of the barrier to internal rotation in ethane remains controversial. This debate centers around the relative importance of hyperconjugation vs steric/exchange interactions in determining the staggered structure and torsional barrier. A distinction between the competing models is that steric interactions primarily depend on the distance between interacting atoms, whereas hyperconj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
33
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 23 publications
1
33
0
2
Order By: Relevance
“…A microwave study of the molecular structure of 3‐hexyne has recently been reported 1. The observed rotational structure can unambiguously be assigned to a syn ‐eclipsed C 2 v conformation.…”
Section: Introductionmentioning
confidence: 99%
“…A microwave study of the molecular structure of 3‐hexyne has recently been reported 1. The observed rotational structure can unambiguously be assigned to a syn ‐eclipsed C 2 v conformation.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23] These last correlations are involved in many important chemical and biological observations like the degree of antimalarial activity of quinine, quinidine, and their diasteromers. [26][27][28] n-C 4 H 10 [29] and C 2 H 5 CBCC 2 H 5 [30] have also been relevant models in the analysis of conformational isomerism for which it has been argued that steric effects are the most important in the determination of the most stable conformers. There is an active discussion about the causes that determine the conformational equilibrium of this molecule.…”
Section: Introductionmentioning
confidence: 99%
“…[24,25] The reasons underlying the preponderance of certain conformers over others have been studied by using different models like ethane. [30,31] Other particularly fundamental examples of conformational analyses are those of substituted cyclohexane rings wherein the conformational preferences of molecules such as CH 3 AC 6 H 11 , (CH 3 ) 3 CAC 6 H 11 , and C 6 H 5 AC 6 H 11 are directly affected by intramolecular noncovalent interactions (INCIs) of the CAHÁÁÁHAC type. Exchange interactions (Pauli repulsion, steric contacts), electrostatics, and hyperconjugation are amongst the many effects that have been used to explain the preference of the staggered over the eclipsed conformation of C 2 H 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Any polarization of the C"C triple bond from cylindrical symmetry by asymmetric alkyl substituents appears to be negligible. This has been demonstrated in 3-hexyne [1] (CH 3 CH 2 C"CCH 2 CH 3 ), which is heavy atom planar with syn-eclipsed C 2v symmetry, and 3-heptyne [2] (CH 3 CH 2 C"CCH 2 CH 2 CH 3 ). In the latter case, the substituted propyl group exists in anti and gauche configurations.…”
Section: Introductionmentioning
confidence: 92%